Phosphatidylinositol phosphate 5-kinase Iβ recruits AP-2 to the plasma membrane and regulates rates of constitutive endocytosis - David Padrón; Ying Jie Wang; Masaya Yamamoto; Helen L. Yin; Michael G. Roth (2003)
Overexpression of phosphatidylinositol phosphate 5-kinase (PIP5KI) isoforms α, β, or γ in CV-1 cells increased phosphatidylinositol 4,5-bisphosphate (PIP2) levels by 35, 180, and 0%, respectively. Endocytosis of transferrin receptors, association of AP-2 proteins with membranes, and the number of clathrin-coated pits at the plasma membrane increased when PIP2 increased. When expression of PIP5KIβ was inhibited with small interference RNA in HeLa cells, expression of PIP5KIα was also reduced slightly, but PIP5KIγ expression was increased. PIP2 levels and internalization of transferrin receptors dropped 50% in these cells; thus, PIP5KIγ could not compensate for loss of PIP5KIβ. When expression of PIP5KIα was reduced, expression of both PIP5KIβ and PIP5KIγ increased and PIP2 levels did not change. A similar increase of PIP5KIα and PIP5KIβ occurred when PIP5KIγ was inhibited. These results indicate that constitutive endocytosis in CV-1 and HeLa cells requires (and may be regulated by) PIP2 produced primarily by PIP5KIβ.